2022
DOI: 10.1021/acssuschemeng.1c06935
|View full text |Cite
|
Sign up to set email alerts
|

Support-Dependent Cu–In Bimetallic Catalysts for Tailoring the Activity of Reverse Water Gas Shift Reaction

Abstract: Cu-based bimetallic catalysts have attracted great attention for the reverse water gas shift (RWGS) reaction due to their high activity and selectivity. This work reports the application of Cu−In bimetallic catalysts for the RWGS reaction and demonstrates that the promotion effect of In on Cu is support sensitive. The Cu−In/ZrO 2 catalyst exhibited significantly higher CO 2 conversion than the Cu/ZrO 2 catalyst, whereas the CO 2 conversion over Cu−In/CeO 2 was much lower than that of Cu/CeO 2 . The reasons of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…116 For example, it was demonstrated that a FeCeO 2 −Al 2 O 3 catalyst could lead to a CO 2 -to-CO conversion of over 70%, which can be further increased by combining Fe with copper. 72 Copper-based catalysts are also frequently used in RWGS operations 64,66,67,72,115 owing to Cu high activity for hydrogen adsorption and dissociation. In this regard, in a recent work by Vu et al, the incorporation of Cu on a Fe-bearing metallurgical residue used as a catalyst support led to the development of a catalyst with excellent potential in the RWGS reaction.…”
Section: Thermochemical Reactionsmentioning
confidence: 99%
“…116 For example, it was demonstrated that a FeCeO 2 −Al 2 O 3 catalyst could lead to a CO 2 -to-CO conversion of over 70%, which can be further increased by combining Fe with copper. 72 Copper-based catalysts are also frequently used in RWGS operations 64,66,67,72,115 owing to Cu high activity for hydrogen adsorption and dissociation. In this regard, in a recent work by Vu et al, the incorporation of Cu on a Fe-bearing metallurgical residue used as a catalyst support led to the development of a catalyst with excellent potential in the RWGS reaction.…”
Section: Thermochemical Reactionsmentioning
confidence: 99%
“…Many bimetallic nanoparticles have recently been studied for the rWGSR, for instance, unsupported FeCo, 31 unsupported CuNi, 32 CuNi on Al 2 O 3 , 33 NiAu on SiO 2 , 34 PtCo on TiO 2 , 35 and CuIn on ZrO 2 . 36 In this study, we consider CO 2 dissociation (reaction eq 2) on (111) surfaces of alloys with up to four elements picked from Au, Ag, Cu, Pt, and Pd. We find multiple alloys with reactivities in between those of Au and Cu, indicating that the discrete reactivities of pure metals become a continuous reactivity distribution in the broad alloy composition space.…”
Section: Figurementioning
confidence: 99%
“…The use of carbon dioxide (CO 2 ) as an abundant C 1 building block for the production of chemicals, materials, and fuels has sparked the interest of scientists because such processes offer a promising way to mitigate the emergent global climate change. , Catalytic CO 2 hydrogenation is a very effective capacity replacement method and a significant tool to achieve “liquid sunshine” fuel . The Cu-based catalysts, bimetallic/noble metals supported on metal oxides, and transition metal carbide-based catalysts are the most commonly utilized catalysts for CO 2 hydrogenation to the C 1 product. Reduced oxides have a great propensity for interacting with CO 2 and are widely used as supports for metal dispersion.…”
Section: Introductionmentioning
confidence: 99%